Pengalaman Ibu Remaja Primipara Memperoleh Dukungan Keluarga Dalam Memberikan Asi Eksklusif : The Experience of Primiparous Teenage Mothers Getting Family Support In Providing Exclusive Breastfeeding - Della Afriani Fauzi; Nurul Ainul Shifa (Open Access Jakarta Journal of Health Sciences, 2022)
Background: The Infant Mortality Rate (IMR) in Indonesia is currently in the range of 30 per 1000 live births and about 5% of deaths are caused by infectious diseases associated with low immunity of infants due to lack of breast milk intake. The experience of primiparous adolescent mothers in obtaining family support in providing exclusive breastfeeding. Objective: This study aims to find out what are the experiences of primiparous adolescent mothers in exclusive breastfeeding and what are the obstacles and lack of family support. Methods: This research is a qualitative research with descriptive phenomenology, data obtained through in-depth interviews with five respondents who are primiparous adolescent mothers who have met the requirements or are said to be saturated. Data were collected in the form of interviews and field notes and analyzed by technique. Results: The experiences of primapara adolescent mothers in exclusive breastfeeding were pain in the breasts, sore nipples and swollen breasts. Teen mothers felt that there was a negative assessment of the social environment with their status as young mothers and some participants expressed their lack of understanding about breastfeeding. The obstacles to exclusive breastfeeding are the reasons for sore nipples, swollen breasts, psychological problems, and working mothers. Husbands do not provide support or motivation for their wives to give exclusive breastfeeding to their children, even their own biological mothers do not give directions to primiparous adolescent mothers to give exclusive breastfeeding. Conclusion: The experience of primiparous adolescent mothers during exclusive breastfeeding is highly dependent on family support, although adolescent mothers know that breastfeeding is important for children's health but the confidence and confidence of adolescent mothers in breastfeeding is still low. The five themes found in this study were able to describe the experiences of primiparous adolescent mothers while receiving family support in exclusive breastfeeding.